Total mercury exposure risk and selenium content measuring on fishery products consumed by women of childbearing age from Bogota, Colombia - Mojica Cortes, Andrea del Pilar; Guerrero Montilla, Jaime Alberto; Sánchez Barrera, Iván Camilo; Vargas Hernández, Jhonny Eddison; Ruíz Pérez, Luz Adriana; Castro Aguilar, Diana Patricia; Noreña Trigos, Oscar Alberto; Castellanos García, Ruth; Pérez Castiblanco, Diana María (Vitae, 2021)
Background. Dietary exposure to mercury in women of childbearing age could result in neurological effects on the fetus. A health risk assessment of total mercury by fishery products intake has not been conducted in this population group in Bogota, Colombia. On the other hand, it has been suggested that selenium content on fishery products may have a protective effect against mercury toxicity. Nevertheless, selenium content on fish species marketed in Bogotá has not been determined. Objective. Exposure risk to total mercury and selenium content on fishery products consumed by women of childbearing age from Bogota, Colombia, were assessed. Methods. Total mercury and selenium concentrations for products available at fish stores and supermarkets were determined. The exposure risk to total mercury was estimated considering the intake of these products by women of childbearing age group. Results. Total mercury highest concentrations were 0.8166 mg/kg in mota (Calophysus macropterus), and 0.6275 mg/kg in catfish (Pseudoplatystoma tigrinum). On the other hand, the highest selenium concentration was 0.6471 mg/kg in nicuro (Pimelodus blochii). Finally, it was established that for women of the childbearing age group, health risk of exposure to total mercury due to mota intake exceeded by 8.56-fold the reference dose. Conclusions. Mota intake considerably increases exposure risk to total mercury on women of childbearing age from Bogota, Colombia. The selenium levels established in the fishery products assessed, except for catfish and mota, are theoretically suggestive of a protective effect of selenium against mercury toxicity. Consequently, continuous total mercury concentrations monitoring is required to protect health of the women of childbearing age and the general population from Bogota, Colombia.